Electro-clinical relationship and source analysis of absence seizures in childhood - Aguilar-Fabré, Liane; Rodríguez-Valdés, René F.; Galán-García, Lídice; Bosch-Bayard, Jorge F.; Hernández-Montiel, Hebert L.; García-García, Ramiro J. (Revista mexicana de neurociencia, 2022)
Abstract Purpose: This study was to deepen into the electro-clinical relationship and source analysis of absence seizures in childhood. Methods: Thirty-three subjects were studied with clinical and electrophysiological diagnosis of absence seizures without antiepileptic medication, video-electroencephalogram was applied. We obtained clinical behavior and electrophysiological variables during seizures and General Linear Model was applied, with p < 0.05. Source analysis was carried out with VARETA method. Results: 174 seizures were evaluated. 75.75% showed interictal epileptiform discharges (IED) and 12.12% showed posterior delta activity. There was an unequal behavior in relation with total electro-clinical seizures and presence or no of IED (p = 0.02), namely between subjects without IED in EEG and multifocal EEG (p = 0.008). Quantity of seizures recorded during HPV had a different behavior between subjects without IED in EEG and multifocal EEG (p = 0.03) and between focal and multifocal EEG (p = 0.04). Source analysis (VARETA) evidence the onset frontal of seizures in 57.47%, mesial and dorsolateral regions in 43% and 57%, respectively. Conclusion: These data suggest that absence seizures are not “generalized” if we considered global cortical activation but rather involve localized discharges from specific cortical regions, mainly frontal lobe.